Evaluation of agricultural soil radiotoxic element pollution around a lignite-burning thermal power plant - Turhan, Şeref (Walter de Gruyter GmbH, 2019)
Abstract Lignite coal is a major and an essential domestic energy source in Turkey. Many environmental problems and human health hazards may arise during lignite coal exploitation, combustion, and waste (fly and bottom ash and slag) disposal. In addition, lignite-burning power plants can be significant contributors to deposition of radiotoxic elements and/or toxic heavy metals on soil and water. The concentrations of thorium (Th) and uranium (U) in a 140 agricultural soil samples collected from the vicinity of a lignite-burning thermal power plant (LBTPP), located in Kangal district of Sivas province in the Central Anatolia region of Turkey, were determined using energy dispersive X-ray fluorescence spectroscopy. The concentrations of Th and U varied from 2.9 to 12.7 μg g−1 with an average value of 5.8 μg g−1 and 0.3–12.3 μg g−1 with an average value of 1.5 μg g−1, respectively. The radiotoxic elements pollution in agricultural soils was evaluated using pollution indices such as geo-accumulation index (I geo), enrichment factors (E F ), pollution index (P I ) and Nemerow integrated pollution index (NIP I ). The average value of I geo, E F and P I estimated for Th and U were found as −1.8, 1.2 and 0.44 and −1.7, 1.7 and 0.58, respectively. The results indicated that the soils around Kangal LBTPP were practically unpolluted to low polluted with Th and U. The NIP I values varied from 0.3 to 4.0 with an average value of 0.6. The evaluation result of NIP I revealed that 86 % of total soil samples were non-polluted.
Keywords: 2. Zero hunger; 13. Climate action; 11. Sustainability; 15. Life on land; 7. Clean energy; 6. Clean water; 3. Good health